ОСОБЛИВОСТІ ФІЛЬТРАЦІЇ МІДІЇ У ДОСЛІДАХ З “ДВОШАРОВОЮ ВОДОЮ” ТА ВПЛИВ СЕЗОННОГО ТЕРМОКЛИНУ НА МІДІЙНІ ПОСЕЛЕННЯ У ЧОРНОМУ МОРІ - Заїка, В. Є. (Marine Ecological Journal, 2023)
The silt form of the mussel Mytilus galloprovincialis inhabits the Black Sea at the depths with the jamp of density, caused by the season thermocline. They created the jump of density in the laboratory (with the help of “two-layer water” according to salinity) and checked an effect of mussels filtration. It has been stated, that the flow from discharging syphon of mollusk did not disturb the boundary between two layers, even when it was located only 10 cm over mussel, with difference in two layers salinity not exceeding 0.5 ‰. Mussels clean from suspension only the lowest water layer. Ecological consequences have been discussed.